2014
DOI: 10.1038/labinvest.2013.128
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment Ki-67 score for prediction of response to neoadjuvant chemotherapy in breast cancer

Abstract: Measurement of Ki-67, a marker of cell proliferation, has been associated with response to therapy, but methods of measurement are controversial. Here we use a quantitative objective measurement for Ki-67 to determine the best method for assessment of Ki-67 for prediction of response to neoadjuvant chemotherapy. Analysis was conducted on a cohort of 105 consecutive invasive breast cancer patients that received neoadjuvant therapy between 2002 and 2010, and on whom pre-surgical biopsies were obtainable. Ki-67 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
70
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(74 citation statements)
references
References 52 publications
3
70
0
1
Order By: Relevance
“…These results are perhaps surprising, given that it is well established that a high Ki67 labeling index is associated with worse prognosis. 16 Nevertheless, it is also known that Ki67 score can be predictive of neoadjuvant chemotherapy response, 29 and mean Ki67 labeling indices have been found to be higher in patients with a pathological complete response after neoadjuvant chemotherapy; this has led to the hypothesis that there may be a high cutoff above which prognosis is better than in patients with lower Ki67 values. 30 As all patients within the cohort in this study received anthracycline-based chemotherapy, 8 our findings that high Ki67 values within the ER-negative subgroup are significantly associated with better overall survival lends tentative support to this hypothesis, and warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…These results are perhaps surprising, given that it is well established that a high Ki67 labeling index is associated with worse prognosis. 16 Nevertheless, it is also known that Ki67 score can be predictive of neoadjuvant chemotherapy response, 29 and mean Ki67 labeling indices have been found to be higher in patients with a pathological complete response after neoadjuvant chemotherapy; this has led to the hypothesis that there may be a high cutoff above which prognosis is better than in patients with lower Ki67 values. 30 As all patients within the cohort in this study received anthracycline-based chemotherapy, 8 our findings that high Ki67 values within the ER-negative subgroup are significantly associated with better overall survival lends tentative support to this hypothesis, and warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Given the hypothesis of a lesser benefit of adjuvant chemotherapy in indolent breast cancer, investigators have searched for molecular markers that may predict response to treatment, with a number of studies indicating a role for Ki-67 (9)(10)(11)(12). In a retrospective analysis of the Breast Cancer International Research Group 001 trial, significantly improved 3-year DFS was observed with docetaxel (T) plus doxorubicin (A) plus cyclophosphamide (C) versus fluorouracil (F) plus AC in patients with luminal B tumors [estrogen receptor (ER)-positive and/or progesterone receptor (PgR)-positive and HER2-positive or Ki-67 !…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that tumours with higher expression levels of Ki67 respond better to adjuvant chemotherapy than those tumour having low levels of Ki67 [11,12]. Ki67 expression is an independent predictive of neoadjuvant chemotherapy in BC patients [13,14]. as well as the neoadjuvant endocrine therapy in postmenopausal patients.…”
Section: Introductionmentioning
confidence: 99%